Initial Assessment the Effects of Polyethylene Microplastics on the Growth of Zebrafish Embryos Danio rerio - Le Dang Khoi, Ta; Thi Thanh Hoai, Nguyen; Xuan Nui, Pham; Lai Thanh, Nguyen; Thi Hai, Do; Thi Thanh Thuy, Tran; Mai Hoa, Nguyen; Thi Thanh Hai, Pham; Huong, Tran Thi Thu (VNU Journal of Science: Earth and Environmental Sciences; Vol 40 No 4DO - 10.25073/2588-1094/vnuees.5218, 2024)
The aim of this study to evaluate the effect of polyethylene (PE) microplastics to mortality rates and morphological changes of zebrafish ( Danio rerio ) embryos by determining the mortality ratio of embryos and changes in embryo morphological structure after 24, 48, 72 and 96 h of exposure. Zebrafish were obtained from the Faculty of Biology - Hanoi University of Science. 24-hour-old fish embryos were exposed to PE microplastic concentrations of 5; 10; 20; 50 and 100 µg/mL. The results showed that when exposed to microplastics at concentrations of 10 µg/mL or higher, only about 5-10% of mortality embryos and the ratio did not increase with increasing concentration. These embryos died in the first 24 h and the number of dead embryos did not increase throughout the experiment. A similar trend was also observed when evaluating the ratio of morphologically abnormal embryos, embryos with abnormal pericardial edema were observed throughout the experiment at the highest concentration of 100 µg/mL. The results showed the potential risk in the using plastic products for the ecological environment.